Provenience, Provenance, and Place-Based Education: An Examination of the Milwaukee County Archaeology Surface Collection at the Milwaukee Public Museum - (:unkn) unknown (My University, 2025)
This thesis contextualizes and documents 436 catalog numbers representing 1,257 archaeological artifacts recovered from Milwaukee County, Wisconsin; these are a subset of a larger collection of 816 cultural items that comprise the Milwaukee County Archaeological Surface Collection (MCASC), currently housed at the Milwaukee Public Museum (MPM). The MCASC contains 83 accessions, accounting for artifacts accumulated from 69 individual donors between 1889 and 2000. This collection is classified as ‘surface collected’ due in part to the fact that these artifacts were found, often by locals, as Milwaukee County developed and became increasingly industrialized. As a result, precise information about the find locations and associated context is often lacking, fragmentary, or incomplete. However, museum registration files and historical archives helped to determine more specific provenance and provenience. Connections are made between this collection and the changing landscape of Milwaukee County, with discussion on urbanization, avocational archaeological collecting practices, and museums as educational collaborators. Accession donor biographies and collection statistics are included. This thesis concludes with a discussion of potential uses and applications of these data and the associated artifacts for Wisconsin Act 31 curricula development, research, exhibits, and future museum planning. Attention is called to the important role that consultation and collaboration with Indigenous source communities can play in collections of this kind.
Keywords: Archaeology; Museum studies; archaeology; Milwaukee County; Milwaukee Public Museum (MPM); place-based education; provenance; provenience